Un palazzo “Modernissimo” per Bologna: architettura, tecnologia e identità urbana nella trasformazione di un teatro e di un cinematografo, tra passato e futuro (Schermi. Storie e culture del cinema e dei media in Italia, 2024)
The early proliferation of cinema theatres in Bologna is closely linked to the city’s urban modern- ization in the early 20th century. This transformation is exemplified by the Palazzo Ronzani and the Cinematografo Modernissimo, which opened in 1915. The creation of this multifunctional building marked a significant transition to modern urban landscapes, fostering social and cultural interac- tions. This article explores the architectural, technological, and urban identity changes introduced by the construction and operation of Ronzani’s building. The resilience and adaptability of the Cine- matografo Modernissimo during challenging times, such as World War I, highlight its importance for Bologna’s history. This significance was rediscovered with the recent restoration and 2023 reopening of the new Cinema Modernissimo in the same building by the Film Archive of Bologna (Cineteca di Bologna).
Keywords: Silent Italian Cinema; 20th Century Architecture; Palazzo Ronzani in Bologna; Cinematografo Modernissimo; Urban Modernization